2012
DOI: 10.1371/journal.pone.0043716
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Population Structure of Indian Golden Silkmoth (Antheraea assama)

Abstract: BackgroundThe Indian golden saturniid silkmoth (Antheraea assama), popularly known as muga silkmoth, is a semi-domesticated silk producing insect confined to a narrow habitat range of the northeastern region of India. Owing to the prevailing socio-political problems, the muga silkworm habitats in the northeastern region have not been accessible hampering the phylogeography studies of this rare silkmoth. Recently, we have been successful in our attempt to collect muga cocoon samples, although to a limited exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
5
8
0
Order By: Relevance
“…Our results coincide with other reports based on single marker systems [9], [10], [11] which provide snapshots of allele frequencies in different populations of A. assamensis . Further research is necessary to understand the role of transposable elements and other genomic mechanism(s) that can influence genetic variability within populations of A. assamensis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results coincide with other reports based on single marker systems [9], [10], [11] which provide snapshots of allele frequencies in different populations of A. assamensis . Further research is necessary to understand the role of transposable elements and other genomic mechanism(s) that can influence genetic variability within populations of A. assamensis.…”
Section: Discussionsupporting
confidence: 92%
“…Moderate genetic distance estimates (Table S5) and its concurrence with geographic distance among populations observed in this study may be attributed to low migration and mixing of the genotypes on a limited geographical scale. The observation that genetic differentiation increased with increasing geographic distance further supports the contention that the wild moths do not migrate far [11], [29], [30]. Analysis with STRUCTURE using ISSR data indicated a putative population structure where wild populations and cultivated populations from Upper Assam and Lower Assam formed discrete clusters (Figure 2B).…”
Section: Discussionsupporting
confidence: 59%
“…SSRs offers several advantages such as their distribution, specificity, and reproducibility, therefore, they were extensively employed in population genetics [8], [9], genetic diversity [10], [11], [12], [13] and evolution [14], [15]. Based on the origin, SSRs has been classified into two types: 1) genomic SSRs (that derived from genome), and 2) EST-SSRs (that comes from expressed sequence tags) [10], [14].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many researchers thought that the altitudinal pattern, habitat fragmentation, location and population size have a highly significant impact on genetic diversity within populations (Arunkumar et al, 2012;Feng et al, 2006;Parvin et al, 2014). In the present study, genetic diversity parameters such as n a , n e , PPB, h and I indicated that the higher genetic diversity exists in populations between 1500 and 1950 m asl, whereas the lower genetic diversity exists below 1280 m asl.…”
Section: Genetic Variability Along the Altitudinal Gradientmentioning
confidence: 99%